EFL Students' Perception Towards Online Learning: What to Consider? - Saputra, Eko; Saputra, Dwi Bayu; Handrianto, Ciptro; Agustinos, Putri (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
The outbreak of the deadly coronavirus at the end of 2019 (Covid-19) has pushed many education institutions to do a radical transformation by moving all forms of their services, particularly teaching from traditional face-to-face mode to completely online foreign language teaching. This research aims to investigate Indonesian students’ perception of online learning and the three most challenging problems they encountered when enrolling in it under the context of English as Foreign Language students. Based on a review of the literature on online learning and students’ perception, a questionnaire was constructed and distributed to 57 students that had enrolled in an online course via google form along with a question asking the three most challenging problems they encountered during the course. Analysis of the responses demonstrated that most of the students had a positive perception of online learning. The three most challenging problems the students encountered were signal (internet connection), money (financial ability), and comprehension (comprehending the course) respectively. The result indicates that online learning can be a reliable solution for the teaching and learning process during a pandemic. However, in applying it, the campus must consider an alternative solution for the students who live in the bad internet connection area. Supporting them with subsidies, or free internet packages can help them to keep studying during a hard time. Lastly, teachers must work hard to ensure that their teachings are understandable so that their students will not get lost during the learning process.